Characteristics of her2-positive breast cancer, and the current use of anti-her2 therapy and its related factors - Le, Phuoc Thanh; Phan, Thien Long; Le, Ha Tuyet Ny; Tong, Ngoc Huong; Tran, Khanh Luan; Ho, Xuan Dung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
<header> </header> Objective: To describe the characteristics of patients with HER2-positive breast cancer and to identify the proportion of patients using anti-HER2 therapy, and treatment-making related factors. Methods: An analytical cross-sectional study was conducted on 79 patients with BC and HER2-positive diagnosed by immunohistochemistry (IHC) or with FISH at the Oncology Department of Hue University of Medicine and Pharmacy Hospital and Oncology Center of Hue Central Hospital from 1/2021 to 12/2022. Clinical and pathological features, type of drug, number of cycles using anti-Her2 therapy were recorded using medical documents. The decision-making related factors were recorded by questionnaire interviewing patients and relatives. Exclusion criteria included recurrent or previously treated tumors; having contraindications with anti-HER2 therapy; not being willing to participate in the study. SPSS 22.0 was used for the analysis. Results: Mean age was 54.14 ± 11.03. Patients with right-sided BC accounted for 53.1%. 60.8% of tumors were located in the upper right quadrant of the breast. Patient’s self-report of lumps was the most common cause of hospitalization (77.2%). By ultrasound, 60.2% of participants had a tumor size of 2 - 5cm. Abnormal lymph nodes were identified in 40.8% of patients. Histopathologically, invasive ductal carcinoma was found in the majority of tumors (75.9%). Stage II was predominant with 59.5% and 7.6% of patients with stage IV. The rate of treatment with Trastuzumab in our study was 27.8%. The main reason that patients refused anti-HER-2 therapy was financial problems (96.5%). The awareness of anti-HER2 therapy among patients and their relatives was significantly associated with the treatment decision (p = 0.007). Conclusion: Regarding the positive-HER2 BC patients, invasive ductal carcinoma was the major histopathological finding. More than half of the patients were classified as stage II of the disease. The rate of patients undergoing antiHER2 therapy was 27.8%. Financial problems were found to be the main reason for refusal of treatment. Awareness of anti-HER2 therapy is significantly associated with the patient’s decision on treatment.